Photocatalytic properties of carbon nanotubes/titania nanoparticles composite layers deposited by electrophoresis. (February 2016) - Scalese, S.; Scuderi, V.; D'Angelo, D.; Buscema, M.M.G.; Libertino, S.; Puglisi, R.A.; Miritello, M.; Privitera, V.
Abstract: A large-scale use of nanotechnology for photocatalysis-based water purification requires to identify simple, reliable and low cost processes for the production of the photocatalytic materials. To this aim we have investigated the possibility to deposit, by electrophoresis, composite layers formed by multi-walled carbon nanotubes (MWCNTs) and anatase-type titanium dioxide nanoparticles (np-TiO2 ), with different weight ratios. This method allows one to obtain photocatalytic layers on any conductive substrates that in principle can be re-used several times. The photocatalytic efficiency for each C-nanostructure/np-TiO2 composite layer is evaluated by measuring the degradation of methylene blue (MB) dye induced by the light of a solar simulator or UVA/blue light irradiation. The morphology and the composition of the deposited layers are studied by scanning electron microscopy and energy dispersive X-ray analyses, respectively, while photoluminescence spectra were acquired in order to explain the different photocatalytic behaviors observed for each material.